Semantically enriched OWL-S Files for Mathematical Web Services - Sheeba, Adlin; Chandrasekar, A; Veerasingam, P (International Journal of Computer Sciences and Engineering, 2013)
A web service is a programmatically available application logic which can be described using Web Services Description Language (WSDL) or Semantic Web Ontology Language which allows software agents to discover, invoke and execute web services automatically. The aim of this paper is to create domain ontology and semantic web services to describe and define the concepts specific to web services for prepositional logic and set theory which comes under discrete mathematics. The resultant semantically enriched web services can be used to characterize the service in a more meaningful way than the existing WSDL thereby opening the possibility to automatic service discovery and use.